Surfacing Identity of Pre-Service Teachers at the Brink of ICT-Based Teaching in the 21st Century - Lasaten, Ronald Candy Santos (Advances in Social Sciences Research Journal, 2017)
Using the descriptive-correlational research design, the study aimed to describe the pre-service teachers’ attitudes towards ICT-based teaching, their perceived readiness and their technological practices in education and determine their degree of relationship with their levels of knowledge on ICT-based instruction. The study involved 285 pre-service teachers of the Mariano Marcos State University College of Teacher Education, Laoag City, Ilocos Norte. A self-assessment checklist was used to gather the needed data. The pre-service teachers’ levels of knowledge on ICT-based instruction were based on their grades in Educational Technology 2 which focuses on ICT integration. Data gathered were treated using mean and chi-square test of independence. Findings reveal that the pre-service teachers think positively towards the use of ICT in teaching and in learning. It is also revealed that the pre-service teachers are moderately ready in terms of using ICT-based strategies and techniques as regards general performance, skills, competencies and internet sourcing. Further, the pre-service teachers think that they are good enough as practitioners of ICT. However, findings show that the levels of knowledge of the pre-service teachers about ICT-based teaching do not significantly relate with their attitudes, perceived readiness, and ICT practices. The study concluded that the pre-service teachers’ have positive attitude towards ICT-based teaching. The pre-service teachers are prepared to face their student s’ learning concerns. They, too, have good ICT practices. Further, the pre-service teachers’ levels of knowledge on ICT-based teaching have no relationship with their attitudes towards ICT-based teaching, their perceived readiness and their ICT practices.